(untitled) (Veterinary Science, 2017)
The primary target of this study was to determine the level of individual elements protection use, in the diverse areas of work of the polled veterinarian in Argentine, as well as the ambient state of maintenance of work, related it to the frequency of pathologies displayed. The retrospective studies of the surveys made to veterinarians in professional exercise, during years 2003 to the 2006 inclusively, revealed events where injuries were taken place and labor diseases that affect workers quality of life. Activities like rectal tact, produced labor injuries in 11,5 % of the polled veterinarians, mainly due to traumas caused by animals. The acute Brucellosis was notified in 4,3 % of the total of received surveys, whereas 12,2 % were notified like chronic brucellosis. In this profession of risk, the development of strategies for diminishing labor dangers, sensitizing businessmen, professionals, students and workers from diverse sectors, is necessary to establish priorities in the use of elements of personal protection, the correct use of the material and work installations.